Characteristics of Thoracic Radiography and Complications of Displaced Endotracheal Tube - Indrastuti Normahayu; S. Khansa Zatalini (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2026)
Accurate assessment of endotracheal tube (ETT) position is essential after intubation because displacement may lead to clinically relevant pulmonary complications, while local real-world data from Indonesian referral hospitals remain limited. This study aimed to identify chest radiographic characteristics and complications associated with displaced ETT in patients at Dr. Saiful Anwar General Hospital, Malang. This descriptive cross-sectional study reviewed electronic medical records and post-intubation chest radiograph archives from September 2023 to September 2024. Among 4,000 patients who underwent ETT placement, 60 patients (1.50%) had displaced ETT. Pulmonary complications were identified in 48 of these patients (80.00%). Pneumonia was the most frequent complication, occurring in 25 patients (52.08%), followed by combined pneumonia and atelectasis in 12 patients (25.00%) and isolated atelectasis in 11 patients (22.92%). Follow-up chest radiography after ETT repositioning was performed in 43 patients, of whom 18 (41.86%) showed radiographic improvement. Although displaced ETT occurred in a relatively small proportion of patients, pulmonary complications were frequent once displacement occurred. These findings highlight the importance of post-intubation chest radiographic evaluation for early detection of displaced ETT and its complications in routine referral hospital practice.